Day clinic vs. hospital care of pneumonia and severe malnutrition in children under five: a randomised trial. Issue 7 (14th May 2019) - Ashraf, Hasan; Alam, Nur H.; Sultana, Marufa; Jahan, Selina A.; Begum, Nurshad; Farzana, Sharmin; Chisti, Mohammod J.; Kamal, Mohiuddin; Shamsuzzaman, Abu; Ahmed, Tahmeed; Khan, Jahangir A. M.; Fuchs, George J.; et al.
Summary: Objectives: To evaluate the clinical outcomes and costs of managing pneumonia and severe malnutrition in a day clinic (DC) management model (outpatient) vs . hospital care (inpatient). Methods: Randomised clinical trial where children aged 2 months to 5 years with pneumonia and severe malnutrition were randomly allocated to DC or inpatient hospital care. We used block randomisation of variable length from 8 to 20 and produced computer‐generated random numbers that were assigned to one of the two interventions. Successful management was defined as resolution of clinical signs of pneumonia and being discharged from the model of care (DC or hospital) without need for referral to a hospital (DC), or referral to another hospital. All the children in both DC and hospital received intramuscular ceftriaxone, daily nutrition support and micronutrients. Results: Four hundred and seventy children were randomly assigned to either DC or hospital care. Successful management was achieved for 184 of 235 (78.3%) by DC alone, vs . 201 of 235 (85.5%) by hospital inpatient care [RR (95% CI) = 0.79 (0.65–0.97), P  = 0.02]. During 6 months of follow‐up, 30/235 (12.8%) in the DC group and 36/235 (15.3%) required readmission to hospital in the hospital care group [RR (95% CI) = 0.89 (0.67–1.18), P  = 0.21]. The average overall healthcare and societal cost was 34% lower in DC (US$ 188 ± 11.7) than in hospital (US$ 285 ± 13.6) ( P  < 0.001), and costs for households were 33% lower. Conclusions: There was a 7% greater probability of successful management of pneumonia and severe malnutrition when inpatient hospital care rather than the outpatient day clinic care was the initial method of care. However, where timely referral mechanisms were in place, 94% of children with pneumonia and severe malnutrition were successfully managed initially in a day clinic, and costs were substantially lower than with hospital admission. Abstract : Objectifs: Evaluer les résultats cliniques et les coûts de la prise en charge de la pneumonie et de la malnutrition sévère dans un modèle de prise en charge en clinique de jour (CJ) (patients ambulatoires) par rapport à des soins hospitaliers (patients hospitalisés). Méthodes: Essai clinique randomisé où les enfants âgés de 2 mois à 5 ans avec une pneumonie et une malnutrition sévère ont été répartis de façon aléatoire en CJ ou à des soins hospitaliers. Nous avons utilisé la randomisation par blocs de longueur variable de 8 à 20 et avons généré des nombres aléatoires par ordinateur qui ont été attribués à l'une des deux interventions. Une prise en charge réussie a été définie comme la résolution des signes cliniques de pneumonie et la sortie du modèle de soins (CJ ou hospitalisation) sans nécessiter un transfert à un hôpital (CJ), ni à un autre hôpital. Tous les enfants du bras CJ et du bras soins hospitaliers ont reçu de la ceftriaxone par voie intramusculaire, un soutien nutritionnel quotidien et des micronutriments. Résultats: 470 enfants ont été assignés aléatoirement soit à des soins en CJ ou hospitaliers. Une prise en charge réussie a été obtenue pour 184 patients sur 235 (78, 3%) en CJ seule contre 201 sur 235 (85, 5%) en soins hospitaliers [RR (IC95%) = 0, 79 (0, 65 ‐ 0, 97), p = 0, 02]. Au cours des six mois de suivi, 30/235 (12, 8%) du groupe CJ et 36/235 (15, 3%) du groupe soins hospitaliers ont nécessité une réadmission à l'hôpital [RR (IC95%) = 0, 89 (0, 67 ‐ 1, 18), p = 0, 21]. Le coût moyen global des soins de santé et pour la société était de 34% plus faible dans le groupe CJ (188 ± 11, 7 USD) que dans le groupe soins hospitaliers (285 ± 13, 6 USD) ( p < 0, 001) et les coûts pour les ménages étaient de 33% inférieurs. Conclusions: La probabilité d'une prise en charge réussie de la pneumonie et de la malnutrition sévère était 7% plus élevée lorsque les soins hospitaliers plutôt que les soins en CJ étaient les moyens initiaux. Cependant, là où des mécanismes de référence rapides étaient en place, 94% des enfants atteints de pneumonie et de malnutrition sévère ont été pris en charge avec succès dans une clinique de jour et les coûts étaient nettement inférieurs à ceux de soins hospitaliers.